Greening improvement scenarios for assessing the potential of urban carbon sinks and runoff reduction - Nuanchan Singkran (Scientific Reports)
Abstract Two scenarios (SC1 and SC2) were developed using i-Tree Eco software to estimate carbon dioxide absorption (CO2abs ) by trees and avoided runoff (AR) in improved urban green areas (increasing the sizes of these areas and planting additional trees) in Thailand for a 50-year forecast (2024–2074). Tree annual mortality rates of 1 and 3% were assigned to SC1 and SC2, respectively. The results indicated the high potential of the country’s green areas as urban C sinks if proper greening improvements are implemented. CO2abs in SC1 increased from 0.32 million metric tons-CO2 equivalent (Mmt-CO2e) in 2024 to 9.24 Mmt-CO2e (a 2787.5% increase) in 2074 and is projected to increase beyond this year. In SC2, it increased from 0.32 Mmt-CO2e in 2024 to 3.66 Mmt-CO2e (a 1043.8% increase) in 2059 and is projected to gradually decline. The maximum AR (76.07 Mm3) was detected in SC1 at the end of the simulation period, but the peak AR (28.15 Mm3) in SC2 was detected in 2067, with a subsequent decline projected. Locally, CO2abs increased from the observed amounts (mainly not more than 5000 mt-CO2e) from 2019 to 2023 to more than 50,000 mt-CO2e in 65 (84.4%) of 77 provinces in Thailand in 2065.